2019
DOI: 10.35944/jofrp.2019.8.1.003
|View full text |Cite
|
Sign up to set email alerts
|

Sports Sentiment and Stock Returns: The Bombay Stock Exchange

Abstract: Problem/Relevance: This study is motivated by psychological evidence of a strong connection between sporting event outcomes and mood. To evaluate this connection, we analyze the Indian stock market reaction to sudden changes in investors’ mood captured by India’s cricket results. By focusing on a rarely studied mood variable and a very infrequently studied stock exchange, this study adds to our understanding of the association between sporting event outcomes and mood. Research Objective/Questions: In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Some other studies, however, do not support the results of this study including the study of Devy and Irawan (2019) who concluded that the ASIAN games had no impact on the stock market and Anghel (2018) who claimed that the impact is weak. In addition, the Indian stock market was concluded to be not affected by the results of the Indian cricket team as reported by Beer and Lin (2019) and Gkillas et al (2020) which is also not supported by the results of this study. Regarding the effect of win and loss on the stock market, the results of this study are not inline with the results of Truong et al (2021) who concluded that losing an international soccer match has a negative impact on the stock prices and the study of Nachimuthu and Selvam (2018) in which the authors claimed that both win and loss of an international one-day cricket match affect the Bombay stock exchange while in this study only loss has a significant and positive impact.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Some other studies, however, do not support the results of this study including the study of Devy and Irawan (2019) who concluded that the ASIAN games had no impact on the stock market and Anghel (2018) who claimed that the impact is weak. In addition, the Indian stock market was concluded to be not affected by the results of the Indian cricket team as reported by Beer and Lin (2019) and Gkillas et al (2020) which is also not supported by the results of this study. Regarding the effect of win and loss on the stock market, the results of this study are not inline with the results of Truong et al (2021) who concluded that losing an international soccer match has a negative impact on the stock prices and the study of Nachimuthu and Selvam (2018) in which the authors claimed that both win and loss of an international one-day cricket match affect the Bombay stock exchange while in this study only loss has a significant and positive impact.…”
Section: Discussioncontrasting
confidence: 82%
“…To test the effect of sport's results on the stock markets, researchers used many quantitative methods including generalized autoregressive conditional heteroskedasticity model (GARCH) (Beer & Lin, 2019;Kashif et al, 2020), linear regression model (Graziano & Vicentini, 2017) and event study (Asim et al, 2021;Galloppo & Boido, 2020;Škrinjarić & Barišić, 2019). The method used in this study, however, was the event study because the population size was small (trading days of the Indian team matches in the world cup) and thus, the other methods used in the literature cannot be utilized.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations